A dimensão da prática profissional do assistente social do PROEJA e PROEJA FIC (Programa Nacional de Integração da Educação Profissional com a Educação Básica na Modalidade de Jovens e Adultos no Nível Fundamental e Médio) no IFSP - Santos, Amanda Machado dos (2013)
This dissertation has as object, the study of the social assistant practice in PROEJA and PROEJA FIC in IFSP (National Program of Integration of the Professional Education in the Basic Modality and the Initial and Continuous Formation in the Federal Institute of Education Science and Technology of São Paulo, in the Portuguese acronym). The IFSP presents itself as a contradictory socio-occupational space: on one hand, serves the interests of capital and on the other, even considered as compensatory policy, it remains an important activity within the education and professionalization for people lower income. Based on the theoretical analysis of empirical data, this study identified objective and subjective contributions in the practice of social assistants, reinforcing the importance of the development and consolidation of the socio-occupational space. The methodology adopted in this research provided better understanding of the limits and possibilities of social assistants professional practice analyzed in the light of empirical categories, such as: the impact of the social assistant practice in PROEJA and PROEJA FIC; professional mediation in PROEJA and PROEJA FIC daily routine, instrumentality, the routine, the relationships with other professionals, among others aspects. In the investigative process, we used primary and secondary sources by conducting semi-structured interviews, group discussion, bibliographical and documental analysis. For the apprehension of the practical dimension of the social assistant, the study prioritized the analysis of strategic actions, procedures and tools used in the planning, organization, implementation and evaluation of actions as well as the identification of principles that guide the design and professional practice in regards to PROEJA and PROEJA FIC. It was verified, despite the limits and contradictions, the existence of progress in the consolidation of professional practice of social assistants and significant socio-occupational space. To the professionals, competes the responsibility of the incorporation of the Social Service premises, seized the objective conditions of social reality, developing a professional praxis oriented and theoretically able to increasingly contribute to the qualification of profession